Formação inicial de professores em tempos de TDIC: uma questão em aberto - Lopes, Rosemara Perpetua; Fürkotter, Monica (Faculdade de Educação da Universidade Federal de Minas Gerais, 2016)
ABSTRACT: This text presents a research that had as main objective to investigate whether the teacher's training, which will work on Basic Education, has included knowledge about Digital Technologies of Information and Communication (DTIC) and under which pedagogical paradigm they are articulated. The documentary analysis initially included the curricula and teaching projects of 123 courses of three public universities from São Paulo state and, afterwards, the pedagogical projects of six Exact Science courses from one of these universities. Curricula analysis has indicated the existence of mandatory and optional disciplines with TDIC, the latter more numerous, in form of: computational content, curriculum, unbound content of the educational field, methodological resource and topic of discussion. Analysis of educational projects highlighted the mathematics courses as those that include training for the use of TDIC, with the articulation between disciplines as common strategy, guided either by the technical rationality or by the practical rationality.

RESUMO: Apresenta-se uma pesquisa que teve por objetivo geral investigar se a formação do professor que atuará na Educação Básica contém conhecimentos sobre Tecnologias Digitais de Informação e Comunicação (TDIC) e sob qual paradigma pedagógico se articulam. A análise documental realizada contemplou, inicialmente, as grades curriculares e os projetos de ensino de 123 cursos de três universidades públicas paulistas e, posteriormente, os projetos pedagógicos de seis cursos da área de exatas de uma dessas universidades. A análise dos currículos indicou a existência de disciplinas obrigatórias e optativas com ocorrência de TDIC, estas últimas, mais numerosas, em forma de: conteúdo computacional, conteúdo programático, conteúdo desvinculado da área educacional, recurso metodológico e tema de discussão. A análise dos projetos pedagógicos evidenciou os cursos de Matemática como aqueles que incluem a formação para o uso das TDIC, tendo como estratégia comum a articulação entre disciplinas, orientada ora pela racionalidade técnica, ora pela racionalidade prática.
INITIAL TEACHER'S TRAINING IN TIMES OF DTIC: AN OPEN QUESTION
Keywords: Teacher's training; Major; Technologies; Formação de professores; Licenciatura; Tecnologias